2010
DOI: 10.1111/j.1537-2995.2009.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

Prion reduction of red blood cells: impact on component quality

Abstract: Prion filtration does not appear to have a detrimental effect on basic in vitro measures of RBC quality or on blood group antigens as assessed by in vitro methods. However, prion filtration using the P-Capt filter results in loss of Hb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 39 publications
1
29
1
Order By: Relevance
“…Quality management data collected at three time points during the study period showed that the mean volume and Hb of prion filtered and standard RCC were comparable and were above the minimum UKBTS specification (National Blood Service, 2005;Wiltshire et al, 2010). This suggests that prion filtration for selected patient groups could be implemented without compromising the Hb content of the component.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Quality management data collected at three time points during the study period showed that the mean volume and Hb of prion filtered and standard RCC were comparable and were above the minimum UKBTS specification (National Blood Service, 2005;Wiltshire et al, 2010). This suggests that prion filtration for selected patient groups could be implemented without compromising the Hb content of the component.…”
Section: Discussionmentioning
confidence: 87%
“…The prion filtration process results in reduced Hb levels due to red cell trapping within the filter (Wiltshire et al, 2010) and further dilution of the product with SAG-M to make the volume up to standard requirements (National Blood Service, 2005), therefore high volume units were selected for manufacture of the prion-filtered units transfused in this study. Quality management data collected at three time points during the study period showed that the mean volume and Hb of prion filtered and standard RCC were comparable and were above the minimum UKBTS specification (National Blood Service, 2005;Wiltshire et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, as the number of reported cases of vCJD declines, manufacturers are losing interest in developing tests. Several filters have been developed that do remove prions along with WBCs, but thus far they appear be only moderately effective (1‐2 logs of reduction) and result in significant loss of RBC and changes to the resulting component 118 . There are no available techniques to inactivate prions in blood components.…”
Section: Creutzfeldt‐jacob Diseasementioning
confidence: 99%
“…The resin also demonstrated the ability to remove endogenous infectivity from hamster leukoreduced RBCs to below the limit of detection of the bioassay used to determine the infectivity titer 11 . RBC storage variables after leukoreduced RBCs were filtered with the P‐Capt prion filter and then stored with either plasma‐CPD or SAGM to outdate have been evaluated 16‐18 . All of the final variables (hemoglobin [Hb] g/unit, hematocrit [Hct], residual WBCs, total volume) as well as end of shelf life product variables (hemolysis, adenosine 5′‐triphosphate [ATP], 2,3‐diphosphoglycerate acid [2,3‐DPG], potassium, and pH) were within the UK and Council of Europe Guidelines 19,20 .…”
mentioning
confidence: 99%